Intensive immunosuppressive therapy for endogenous lipoid pneumonia associated with rheumatoid arthritis. Issue 6 (2nd November 2018) - Morita, Hiroko; Arai, Satoko; Kurasawa, Kazuhiro; Okada, Harutsugu; Tanaka, Ayae; Yamazaki, Ryutaro; Owada, Takayoshi; Maezawa, Reika
Abstract: Endogenous lipoid pneumonia is an uncommon inflammatory pulmonary disease that is caused by lipids from an endogenous source, the treatment for which has not been established. We report the first case of endogenous lipoid pneumonia presenting as lung consolidation and which was associated with rheumatoid arthritis. Treatment was successful with intensive immunosuppressive therapy. When a physician finds lung consolidation in a patient with active rheumatic disease, lipoid pneumonia should be considered.